Sensory Priming: The olfaction as an attention inducer - Carolina Roberto Carrieri; Airton Rodrigues; Patricia Santos Lopes; Newton Andréo-Filho; Yasmin Rosa Santos; Orpheu Bittencourt Cairolli; Milica Stevic; Marcelo Dutra Duque; Paulo Roberto Regazi Minarini; Vânia Rodrigues Leite-Silva (Universidade de São Paulo, 2023)
Abstract In this study, we investigated the influence of the olfactive stimulus on visual attention. Two groups of 30 subjects participated in two experiments. Both experiments presented two arrays of fruits stimulus intercalated by an olfactive intervention. The stimulus was received in the form of images by the first group and in the form of words by the second group. An eye-tracking device monitored the timekeeping of visual attention dispensed in each stimulus. The results showed that olfactive priming influenced visual attention in both cases but with a greater degree in the images stimulus group. This study shows for the first time that image information is more susceptible to priming olfactive information than wording information. This effect may be associated with the formation of mental images in working memory, aroused by fragrances.